2010
DOI: 10.1093/molbev/msq206
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Specific Variation in Intensity of Natural Selection in Mammals

Abstract: The molecular clock hypothesis states that protein-coding genes evolve at an approximately constant rate. However, this is only expected to be true as long as the function and the tertiary structure of the molecule remain unaltered. An important implication of this statement is that significant deviations in the rate of evolution of a gene with respect to the species clock are likely to reflect functional and/or structural alterations. Here, we present a method to identify such deviations and apply it to a dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 61 publications
2
42
0
Order By: Relevance
“…33) compared with other mammals concurs with the deterministicstochastic hypothesis (32). However, rapid sequence evolution in the mouse lineage is well known, and need not indicate a release of selection, but, rather, is likely an effect of their short generation time (34,35). As an example, an assessment of selection using dN/dS values (988 genes) has shown that mice (M. musculus) exhibit lower average values than other mammals such as pigs (Sus scrofa) and humans (Homo sapiens), suggesting greater purifying selection, and thus inconsistent with the extensive release of constraint predicted by the deterministic-stochastic hypothesis (ref.…”
Section: Evaluation Of the Pgc-specification Hypothesissupporting
confidence: 69%
See 1 more Smart Citation
“…33) compared with other mammals concurs with the deterministicstochastic hypothesis (32). However, rapid sequence evolution in the mouse lineage is well known, and need not indicate a release of selection, but, rather, is likely an effect of their short generation time (34,35). As an example, an assessment of selection using dN/dS values (988 genes) has shown that mice (M. musculus) exhibit lower average values than other mammals such as pigs (Sus scrofa) and humans (Homo sapiens), suggesting greater purifying selection, and thus inconsistent with the extensive release of constraint predicted by the deterministic-stochastic hypothesis (ref.…”
Section: Evaluation Of the Pgc-specification Hypothesissupporting
confidence: 69%
“…34; see also ref. 35). Mice may be subjected to more restrained evolution than some other mammals simply due to their very large population sizes (34).…”
Section: Evaluation Of the Pgc-specification Hypothesismentioning
confidence: 99%
“…One of the key issues in biology, is understanding how natural selection drives gene functional diversification across different species and lineages [24]. The varying substitutions of amino acids within and across species might be as a result of separate divergence from their common ancestor.…”
Section: Discussionmentioning
confidence: 99%
“…For dN and dS, the former is considered to be related mainly to functional constraints (Kawahara and Imanishi, 2007), while the latter by purifying selection (Smith et al, 2008;Toll-Riera et al, 2011). For this reason, the nearly constant dN and significantly lower dS values of ND4 in the balitorid lineage suggests that it was mostly affected by relaxed purifying selection in this lineage.…”
Section: Lineage-specific Evolution Of Genes In Balitorid Fishesmentioning
confidence: 99%
“…Therefore, variation in evolutionary rates (e.g. dN/dS ratio), especially those between taxa sufficiently closely related (for example within mammals), is considered a strong indicator of anagenesis driven by selection pressure over time (Czelusniak et al, 1982;Kawahara and Imanishi, 2007;Lynch and Conery, 2000;Toll-Riera et al, 2011). This variation of possible factors is hypothesized to have contributed greatly to the function differentiation we observe today in the genes and diversification of organisms (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%